A moral–theological analysis of unethical business practices in Warri through the lens of Proverbs 11:1–6 - Uroko, Favour C. (Verbum et ecclesia, 2022)
Few studies have examined unethical business practices in Nigeria, and no study has examined unethical business practices in Warri local government area of Delta State from the lens of Proverbs 11:1-6. A reading of Proverbs 11, beginning from verse one, reveals that a false balance is an abomination to the Lord, but a just weight is his delight. It further mentions how God hates dishonesty and lack of integrity in whatever form, which in this context is the business environment. The rate of fraudulent business activities in markets across Warri is alarming. Indeed, promoters and culprits of counterfeit goods, such as food, pharmaceuticals, electrical appliances and wire are boldly counting their profits and laughing all the way to the bank in amusement at those who have decided not to join them. This study explores the consequences that await these promoters and culprits of unethical business practices. Literary analysis was used through a phenomenological approach in this context. The recommendations given, as expected, will shed light for the promoters on how to escape the consequences of their actions, and it also encourages those who are determined to maintain their integrity by refusing to engage in these unethical business practices. Intradisciplinary and/or interdisciplinary implications: Proverbs 11 warns that those who engage in unethical business practices will eventually face the wrath of God, which may be expressed through their exposure to law enforcement agencies and the loss of all the riches that will not deliver them when they are caught.